Parenting styles and adolescent coping methods: a comparative study of non-suicidal self-injury and distinct groups - Beini Wang; Lixian Chen; Changzhou Hu; Zhenyu Hu; Wenwu Zhang; Fang Cheng; Lingjiang Liu (BMC Psychiatry)
Abstract Background The global incidence rate of Non-Suicidal Self-Injury (NSSI) is increasing year by year, especially in the adolescent population, where it is highly correlated with parental rearing patterns and adolescent coping styles. Exploring this correlation is crucial for understanding and intervening in NSSI behaviour. Objective This study investigates the nuanced impact of parental parenting styles on coping strategies in adolescents, specifically contrasting these effects between NSSI and non-NSSI populations. Methods A cross-sectional survey was conducted on NSSI patients diagnosed at Ningbo Kangning Hospital in China from June 2020 to December 2021, as well as healthy adolescents from three junior high schools and three high schools in Ningbo City. The total sample consisted of 622 adolescents, aged 11 to 18, including 311 in the NSSI group (280 females, 31 males) and 311 in the non-NSSI group (269 females, 42 males). Data including family background, parenting styles, and adolescent coping strategies were collected. Descriptive statistics, chi-square test, independent samples t-test, correlation analysis, and stepwise regression analysis were used to analyse the data. Results The study found significant correlations between family disharmony, parental education level, and NSSI behaviour. In non-NSSI adolescents, excessive maternal preference was negatively linked to problem-solving abilities, while in NSSI adolescents, negative parenting styles were associated with emotional-oriented coping strategies. Conclusion The findings highlight critical differences in how parenting styles influence coping strategies in NSSI versus non-NSSI adolescents. This underscores the importance of positive parenting in preventing NSSI and suggests that psychological interventions should focus on enhancing emotional support and understanding from parents to foster healthier coping mechanisms in adolescents.